Persepsi Mahasiswa Universitas Wisnuwardhana Malang terhadap Minat Belajar Mata Kuliah Pendidikan Kewarganegaraan (PKn) - Samosir, Tiur Meida; Pribadi, Nukhan Wicaksana (Jurnal Likhitaprajna, 2023)
Citizenship Education is education that examines and discusses government, constitution, democratic institutions, rule of law, human rights, rights and obligations of citizens and the democratic process. Aims to form a better citizen (a good citizen) and prepare them for the future. The aims of this study were (1) to find out the perceptions of Wisnuwardhana University students towards the Citizenship Education course. (2) To find out students' learning interest in taking Citizenship Education courses which are low and often less desirable. (3) To find out the factors that cause and influence the low learning interest of students taking Citizenship Education courses. The approach and type of research used is qualitative. The results of the study were: (1) Perceptions of students at the Wisnuwardhana University of Malang on their interest in studying Citizenship Education courses. Citizenship Education is a very important and mandatory subject for all students from all faculties and study programs in hiding moral values. It is very important for the formation of individuals who have good character, are patriotic, love their homeland and have a strong sense of nationalism in accordance with Pancasila and the 1945 Constitution. Students participate enthusiastically. However, there are still students who have the perception that the Citizenship Education course is a subject that is often taught (at every level of education). The teaching material is generally the same, the material is too heavy and dominated by memorization. so that they have low motivation and enthusiasm in participating in Citizenship Education courses. (2) The interest of students in participating in Citizenship Education courses can be said to be quite good, this is shown by the students being very enthusiastic in participating.